Effects of nano-filler morphology on PU-composites for compression sleeves - Nur Muhammad Sharifuddin (2015)
The burgeoning rise in performance enhancing products calls into play the need for betterment of the current commercial ones. This study seek to ultimately contribute to the continual improvement of the compression garment, more specifically, the arm sleeve. A series of synthesis between a baseline polyurethane and a list of commercial fillers- and one non-commercial- were adopted in this study to investigate the effects of distinctive fillers with variable morphology on the properties of polyurethane. Fillers utilised in this testing were: Layered structure OMMT- Cloisite 30B; spherically shaped nanosilica; plate shaped graphene oxide (GO), rod-shaped carbon nanotubes (MWNT); and fibrous electrospun polylactic acid (PLA). A relationship was established between the final mechanical properties of the PU composite with the morphological identity of the fillers incorporated into the pristine PU matrix: particles with higher aspect ratios- CNT- resulted in superior strength improvements, but often to the expense of material’s ability to stretch. The importance of aspect ratio on the performance enhancement capabilities of fillers extends similarly to the thermal properties with the higher aspect ratio particles displaying the greater improvements in the onset temperature, and crystallization temperature while largely having similar melting temperatures as the baseline PU. Also conducted in this study, was an investigation into the effects of loadings on the final properties of the baseline polyurethane. Fraction loading of 3 different degrees: 0.1%, 1%, 5%, 20% of Cloisite 30B and nanosilica yielded the following findings: Tensile tests found increase in load resulted in a proportional increase in the Young’s Modulus and tensile strength, often compromising the elasticity of the material by the same level of proportionality but in reverse. The effects of loading on the performance enhancement capabilities of fillers extends similarly to the thermal properties with the higher aspect ratio particles displaying the greater improvements in the onset temperature, while largely having similar melting temperatures as the baseline PU. However, crystallization temperature retarded with increase in volume fraction loading. We can attribute certain anomalies discovered in this study to the agglomeration of particles due to the lack of proper dispersion. Also, in an effort to accord similar hot-pressing conditions to all samples to establish similar thermal histories, the thickness of the samples used for tensile testing varied quite significantly. Future studies should consider achieving both aspects for a more accurate comparison of mechanical properties. Future work should also identify the filler with the best compromise between strength and elongation be hot-pressed onto a compression garment itself and donned by an athlete to test for sensorial feedback, as well as the ideal degree of stretch and resistance required.